Small biochar addition enhanced anammox granular sludge system for practical wastewater treatment: Performance and microbial community. (November 2022) - Xie, Junxiang; Cao, Qianfei; An, Tianyi; Mabruk, Adams; Xie, Jiawei; Chang, Yaofeng; Guo, Menglei; Chen, Chongjun
Graphical abstract: Highlights: Peach biochar reactor had better performance in AnGS properties and nitrogen removal. High organic carbon inhibited AnAOB and B/N had the most significant effect on AnAOB. A moderate amount of organic matter promoted the proliferation of AnAOB. Peach biochar reactor had the higher abundance and stronger activity of AnAOB. Abstract: Anaerobic ammonium oxidation (Anammox) granular sludge (AnGS) has poor strength and is prone to disintegration under complex environmental conditions, especially in the presence of complex organic carbon, which renders the Anammox process instable. Herein, with a mixture of landfill leachate and domestic sewage as wastewater, the effect on the properties of AnGS with two small particle size (0.1–0.2 mm) biochars (coconut and peach biochars) addition were investigated at different COD concentrations (150 mg·L −1, 200 mg·L −1, and 250 mg·L −1 ), as well as at different BOD/TN (B/N) (0.3 and 0.5). Results showed that the nitrogen removal efficiencies decreased from 89 % to 72 % as the COD concentration increased by 100 mg·L −1, while peach biochar reactor had better nitrogen removal performance. Excessive organic carbon supply inhibits AnAOB proliferation and B/N had the most significant effect on AnAOB (p < 0.05). The Polymerase Chain Reaction (PCR) indicated peach biochar reactor get higher activity of anammox-related functional genes ( hzs A, hdh ).